2023
DOI: 10.3389/feart.2023.1127078
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests and theoretical analysis for mechanical behaviors of side wall opening construction in mined excavation subway station

Abstract: The connection of subway stations to surrounding underground spaces inevitably involves opening construction in the existing underground structure. The opening construction can strongly impact the existing underground structure when there is no reserved condition. In this study, three-dimensional numerical simulation, model test, and theoretical analysis are used to analyze the mechanical behaviors of side wall opening construction in a mined excavation subway station-Xuanwumen Station of Beijing Subway Line 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Wang [19] pointed out that the opening of the side wall would lead to the redistribution of internal forces in the existing station structure, and it was necessary to control the opening size and the clear distance between adjacent openings to reduce the adverse effects brought by the side wall opening. Hu et al [20] analyzed the influence of side wall opening on the force and deformation of station structure and found that the deformation increment met the requirements while the stress increment was higher than the control requirements and suggested that the limit opening span of side wall should be 5.75m when there was no reinforcement. On the other hand, scholars have also studied the influence of reconstruction and expansion construction of existing stations on the force of the original structure and put forward corresponding construction suggestions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Wang [19] pointed out that the opening of the side wall would lead to the redistribution of internal forces in the existing station structure, and it was necessary to control the opening size and the clear distance between adjacent openings to reduce the adverse effects brought by the side wall opening. Hu et al [20] analyzed the influence of side wall opening on the force and deformation of station structure and found that the deformation increment met the requirements while the stress increment was higher than the control requirements and suggested that the limit opening span of side wall should be 5.75m when there was no reinforcement. On the other hand, scholars have also studied the influence of reconstruction and expansion construction of existing stations on the force of the original structure and put forward corresponding construction suggestions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%